Geographic mapping of head and neck cancers in Nanded, Maharashtra, India: A hospital based study - Namdhari, Balkrishna Harishchandrarao; Deshpande, Shubha Arvind (Tropical Journal of Pathology and Microbiology, 2016)
Background: Head and neck cancers are most common in developing countries. It is the most common cancer of males in India and fifth in females. India is classified as a lower middle income group country by World Bank. Nanded, Maharashtra, India is a district place where this government medical college and hospital is situated; this is a tertiary medical care centre and caters nearby districts like Parbhani, Hingoli, Yavatmal and Adilabad. Methods: This is cross sectional study of 18 months. Cases are selected with superficially palpable head and neck lesions referred to Cytology OPD, and hospital ward with clinical diagnosis of any head and neck neoplastic lesions. An FNAC smear in the Cytology section of CCL and in ward finally the microscopic verification is done by biopsies with histopathological confirmation is done and confirmed cases are included in this study. Geographical mapping done by making the master chart of patient’s permanent addresses. Patients categorized as per codes by NCRP used for Atlas of cancer of India. Results: Relative proportion percentage of head and neck cancers is 88.33 were from Nanded district, followed by Hingoli, Parbhani, Yavatmal from Maharashtra state and Adilabad districts from Telangana state. Conclusions: This centre caters more than five districts including Maharashtra and Telangana state, in this hospital based ‘head and neck cancer registry’ of microscopically confirmed cancers, maximum cases are from Nanded district. This institute does not cover the geographic area mentioned in the literature of highest and lowest relative proportion percentage of head and neck cancers.